2019
DOI: 10.1186/s12903-019-0959-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between malocclusion, caries and oral hygiene in children 6 to 12 years old resident in suburban Nigeria

Abstract: BackgroundThere are conflicting opinions about the contribution of malocclusions to the development of dental caries and periodontal disease. This study’s aim was to determine the association between specific malocclusion traits, caries, oral hygiene and periodontal health for children 6 to 12 years old.MethodsThe study was a household survey. The presence of malocclusion traits was assessed in 495 participants. The caries status and severity were assessed with the decayed, missing, and filled teeth (dmft/DMFT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
6

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 27 publications
0
28
0
6
Order By: Relevance
“…Complications such deviation of the jaw and temporomandibular joint problems are common if premature contact on occluding teeth found [13]. Other issues include difficulty in maintaining oral hygiene such as brushing and flossing around the misaligned teeth that give rise to caries and gingivae problems [14].…”
Section: Discussionmentioning
confidence: 99%
“…Complications such deviation of the jaw and temporomandibular joint problems are common if premature contact on occluding teeth found [13]. Other issues include difficulty in maintaining oral hygiene such as brushing and flossing around the misaligned teeth that give rise to caries and gingivae problems [14].…”
Section: Discussionmentioning
confidence: 99%
“…Bechtold and Briegleb (2010) reported that higher plaque accumulation was noticed in the region of malocclusion. Kolawole and Folayan (2019) showed that moderate to severe gingivitis was present among patients with an anterior open bite.…”
Section: Resultsmentioning
confidence: 99%
“…Six permanent tooth (3, 8, 14, 19, 24, and 30) surfaces were scored on a scale of 0 to 3. The mean scores indicated as DI and CI [ 35 , 36 ]. The sum of DI and CI was defined as OHI-S, which was then categorized into two groups for analysis: (OHI-S ≤ 1.8, and OHI-S > 1.8).…”
Section: Methodsmentioning
confidence: 99%